TAXONOMIC COMPOSITION OF THE HOLARCTIC GROUP OF AREAS OF PLANT GROUPS OF TECHNOGENIC ECOTOPES OF THE KRYVBAS DUMPS (Ecological Bulletin of Kryvyi Rih District, 2024)
The article highlights aspects of the theory of composition of communities, which is the resulting expression of their development, a consequence of the manifestation of species’ adaptive capabilities as components of many variations in forms of living matter in the biosphere. It is noted that analyzing taxonomic composition and construction of taxon spectra of plant communities is a necessary initial stage in understanding their structure, connection systems, potential opportunities, development trends, optimization and conservation. It is determined that specifying the taxonomic composition of plant communities of technogenic ecotopes of dumps at the level of their chorological components is a logical integral direction for the development of the theory of ecological and taxonomic spectra.Research has established that the taxonomic composition of the Holarctic range group consists of 165 species, 130 genera, and 39 families of angiosperms. The leading families of the general taxonomic spectrum of Holarctic angiosperms in terms of the number of species and genera are Asteraceae, Lamiaceae, Poaceae, Fabaceae, Boraginaceae, Brassicaceae, Rosaceae, Chenopodiaceae, Caryophyllaceae. They include 66,68% of the taxonomic spectrum of species of the Holarctic range group and 70,78% of the taxonomic spectrum of genera. The taxonomic spectrum of species of the Holarctic range group is characterized by the dominance in terms of the number of species and genera of a few families and a fairly high proportion of families represented by one species or one genus. The leading families retain their leading positions in terms of the number of genera, but there is no clear advantage of individual genera in terms of the number of species. The most species-rich genera of angiosperms of the Holarctic range group are Artemisia L., Centaurea L., Euphorbia L., Acer L., Ulmus L. The highest rates of participation of representatives of the Holarctic range group are in the spectra of taxa (species, genera, families) of communities of terrace sites and plateau-like peaks, and the lowest ones are in the taxon spectra of communities occurring the slopes of technogenic stows. The proportion of Eurasian, Holarctic, European, Palearctic plants having extended spectra of taxonomic volume in the taxonomic spectra is significant, etc.The prospects for further studies of the features of the Holarctic component of serial plant communities of dumps with detailing the features of the taxonomic fund for individual stows and their zones, with specification at the level of chorological groups, ecomorphic capacity, florogenetic relations of taxa, the distribution specifics, economic assessment of species and the development of zonally expedient ways to optimize the vegetation of technogenic ecotopes in disturbed lands are determined.
Keywords: plant communities (groups), dumps, technogenic ecotopes, composition, а group of ranges (habitats), chorological group, a taxon, spectra.